Charcoal Joe [large type] : an Easy Rawlins mystery - Mosley, Walter (Mosley, Walter. Easy Rawlins mystery, 2016)
"Easy Rawlins is back, with a new detective agency and a new mystery to solve. Charcoal Joe has asked Easy to help clear Joe's son, who was found standing over a white man's dead body in his cabin home"--